A METHOD OF LOADING UNIT FORMATION TAKING INTO ACCOUNT MASS, LOAD-BEARING STRENGTH AND SURFACES OF PACKING UNITS - Kamil POPIELA; Mariusz WASIAK (Scientific Journal of Silesian University of Technology. Series Transport)
The problem of loading unit formation is computationally complex in nature. This article presents a heuristic algorithm of forming unit loads, which can be applied to unit load arrangement on unit load devices. This method accounts for dimensional, mass and load-bearing strength of loading units and loading devices. Moreover, the rotation of packages about a 90° vertical axis has been made possible. In this algorithm, the bearing surface of each packing unit is entirely supported. This guarantees the stability of additional unit load layers. A sample calculation of the arrangement of 30-unit loads is presented in this article.